Caregiving burden and special needs of parents in the care of their short-statured children – a qualitative approach - Lackner, Lea; Quitmann, Julia Hannah; Witt, Stefanie (Frontiers in Endocrinology, 2023)
Purpose To explore caregiving burden, health-related quality of life (HRQOL), stress, and individual resources of parents in the care of children with isolated growth hormone deficiency (IGHD) or idiopathic short stature (ISS). Methods Focused interview analysis of previously, within the Quality of Life in Short Stature Youth (QoLISSY) project, conducted structured focus group discussions (n=7) with parents (n=33) of children with IGHD/ISS aged 4 to 18 years were performed. Results 26 out of the 33 parents reported mental stress due to their child’s growth disorder. Social pressure and stigmatization were also mentioned as being demanding. Some parents reported having trouble with human growth hormone (hGH) treatment. Several parents wished for parent support groups with other like-minded parents of short-statured children. Conclusion For physicians, it is essential to understand the parents’ caregiving burden, stress, and individual resources in caring for IGHD/ISS children. If an impaired HRQOL is detected, psychological intervention for these parents may be scheduled, and coping mechanisms may be discussed. Furthermore, it seems essential for parents to be educated by their healthcare provider about the possible side effects of hGH treatment or to know where to find evidence-based information about it.